Rapid detection assays for food and water ; For food and water. (Special publication., 2001)
The detection of harmful chemicals and microbial pathogens in food and water destined for consumers is of paramount importance the world over and it is vital that new techniques and discoveries are widely disseminated. Bringing together international experts in the field, Rapid Detection Assays for Food and Water presents original, state-of-the-art research and a review of the established methods in this key subject area. Covering the four main areas of water microbiology, water chemistry, food microbiology and food chemistry, the book discusses highly sensitive chemical and biological detectio.